Let's Talk LMCC (S01E05): 37-2 Antihyperglycemic Agents - Meryem K. Talbo; Tricia Peters; Susan Joanne Wang; Esther SH Kang; Renée-Claude Bider; kath Lan; Samy Amghar; Vanessa Ross; Masha Samuel; Khiran Arumugam; Jan Pack (McGill Journal of Medicine)
Welcome to the McGill Journal of Medicine (MJM) LMCC review. This podcast series was created to aid medical students studying for the Canadian Medical Council (MCC)’s licensing exam. Each episode is created based on specific LMCC objectives and is divided into 2 parts. In part one we provide an overview of the topic with the help of experts in the field, followed by Part 2 where we review LMCC styled questions to help consolidate knowledge. In this episode, we welcome our expert advisor, Dr. Tricia Peters, Endocrinologist and Associate Professor in the Faculty of Medicine and Health Sciences at McGill University to complete our series on LMCC Objective 37-2: Diabetes Mellitus by speaking about antihyperglycemic agents. This episode was written by Susan Wang, Meryem Talbo and Dr. Tricia Peters, with feedback from the entire MJM Podcast Team.